Does awareness lead customers to use sustainable banking services? A study using path analysis - E. S. Sina; D. Vennila (Heritage and Sustainable Development)
With the global transition of the traditional triple bottom line framework of Planet, People, and Profit to the Environmental, Social, and Governance (ESG) paradigm, it has become imperative for banks to incorporate sustainability within their operations and beyond. The disclosure of the ESG framework and responsible lending has significantly impacted banks’ financing choices, particularly in environmentally sensitive regions. This study assesses customers' awareness and usage of sustainable banking services. A structured survey was conducted among 200 customers from 10 commercial banks (20 each from 10 banks) in Coimbatore, India. The questionnaire method was adopted to collect the data. Based on the sustainability theory, the study intends to investigate customers' awareness and usage of sustainable banking services using a path analysis approach. The results show that awareness has a significant direct influence on the usage of sustainable banking services, and this understanding will help in designing a future sustainability framework. This is insightful advice on how policymakers, financial organizations, regulators, and bank managers can create and execute successful designs for sustainable banking operations.